2003
DOI: 10.1007/s00330-002-1670-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of liver metastases by pulse inversion harmonic imaging during Levovist late phase: comparison with conventional ultrasound and helical CT in 160 patients

Abstract: The aim of this study was to evaluate capabilities of pulse inversion harmonic imaging (PIHI) with Levovist in detection of liver metastases compared with conventional ultrasound (US) and helical CT (HCT). One hundred sixty consecutive patients with known malignancies were evaluated by conventional US, PIHI 2 min (40 patients) or 4 min (120 patients) after Levovist injection and HCT. Conspicuity and number of the identified metastatic lesions were evaluated and assessed by statistical analysis (significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 20 publications
2
10
0
1
Order By: Relevance
“…Findings in previous studies documented that both subjective and objective conspicuities of liver malignancies are increased in late-phase PIHI compared with fundamental sonography. 3,6,7,13 Similarly, in our study we reported new lesions on late-phase PIHI in 4 patients (12.5%). In 3 of them, new lesions detected with PIHI were barely seen on a retrospective evaluation of fundamental sonography.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Findings in previous studies documented that both subjective and objective conspicuities of liver malignancies are increased in late-phase PIHI compared with fundamental sonography. 3,6,7,13 Similarly, in our study we reported new lesions on late-phase PIHI in 4 patients (12.5%). In 3 of them, new lesions detected with PIHI were barely seen on a retrospective evaluation of fundamental sonography.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is notable given the importance of accurate staging of patients with malignant disorders for selection of appropriate treatment strategies. Previous studies have also revealed improved conspicuity of lesions with contrast-enhanced PIHI compared with conventional sonography in patients with malignancies [3][4][5][6][7][8] ; however, those examinations were performed in patients with known or suspected liver metastasis. Unique to our study was the detection of lesions that were undetectable on routine conventional abdominal sonography.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations